Impact of climate change on groundwater resource in a region with a fast depletion rate: the Mississippi Embayment - Ying Ouyang (IWA Publishing, 2021)
Mississippi Embayment (ME) is one of the fastest groundwater depletion regions around the world, while the impacts of climate change on groundwater resources in the region are complex and basically unknown. Using the U.S. Geological Survey's Mississippi Embayment Regional Aquifer Study (MERAS) model, such a challenge was addressed through the base, wet, and dry simulation scenarios. Over the 137-year simulation period from 1870 to 2007, the cumulative aquifer storage depletions were 1.70 × 1011, 1.73 × 1011, and 1.67 × 1011 m3, respectively, for the base, dry, and wet scenarios. As compared with that of the base scenario, the aquifer storage depletions were only 1.76% more for the dry scenario and 1.8% less for the wet scenario. A multiple regression analysis showed that the aquifer storage depletion rate was controlled more by the groundwater pumping and stream leakage rates and less by the groundwater net recharge rate. Groundwater table variation in the forest land was much smaller than in the crop land. Results suggested that groundwater pumping rather than climate change was a key driving force of groundwater depletion in the ME. Our findings provide a useful reference to water resource managers, foresters, and farmers in the ME and around the world when developing their groundwater supply strategies. HIGHLIGHTS One of the world largest groundwater models (i.e., MERAS) was applied.; Agricultural pumping rather than climate change is a key driving force of groundwater depletion.; Aquifer storage depletion was controlled by the groundwater pumping and stream leakage.; Groundwater table variation in the forest land was much smaller than in the crop land.;